On Commutative Systems of Nonselfadjoint Unbounded Linear Operators - Zolotarev, V. A. (Журнал математичної фізики, аналізу, геометрії, 2009)
For a commutative system of nonselfadjoint unbounded operators $A_1$, $A_2$ the concept of colligation and associated open system is given. For these open systems, the consistency conditions are established and the conservation laws are obtained. Mathematics Subject Classification: 47A48.